Encephalopathy with Periodic Discharges In chronic Kidney Disease Patient - Abraham, Miny; Nikhil, Gladson (Nepal Journal of Neuroscience, 2025)
Analysis of spontaneous EEG activity is an essential method in evaluation of patients with impaired consciousness in both acute care and chronic settings. It continues to be the only method that allows the bedside monitoring of both immediate and longterm cortical functioning associated with the conscious or unconscious state.We report two cases of encephalopathy with periodic discharges in chronic kidney disease patients;